2016
DOI: 10.14295/cs.v7i1.865
|View full text |Cite
|
Sign up to set email alerts
|

Between-row spacing and local accession on the yield and quality of garlic

Abstract: Garlic is primarily grown for its cloves used mostly as a food flavoring condiment. Previous studies carried out on plant density indicate its direct influence on yield. Plant density depends on the genotype, environmental factors, cultural practices, etc. This study was established to determine the effects of different between-row spacing on growth, yield, and quality of four local accession of garlic. It was laid out on two-factorial Randomized Complete Block Design with three replications during two years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…The results obtained are in conformity with the findings of Singh et al, (1995), Muro et al (2000). Alam et al,(2010), Moravcevic et al (2011), Olfati et al, (2016) and Azza and Naglaa (2016). 3-Effect of garlic cropping system: 3-a-Germination percentage and some vegetative growth components: Data presented in Table (1) showed that germination % and all vegetative growth characteristics were significantly affected by cropping systems during the two growing seasons.…”
Section: -B-yield and Its Componentssupporting
confidence: 92%
“…The results obtained are in conformity with the findings of Singh et al, (1995), Muro et al (2000). Alam et al,(2010), Moravcevic et al (2011), Olfati et al, (2016) and Azza and Naglaa (2016). 3-Effect of garlic cropping system: 3-a-Germination percentage and some vegetative growth components: Data presented in Table (1) showed that germination % and all vegetative growth characteristics were significantly affected by cropping systems during the two growing seasons.…”
Section: -B-yield and Its Componentssupporting
confidence: 92%
“…Similar results were obtained by Shuab et al 45 , who pointed out that the onion plant is highly responsive to several AMF, which tend to associate with onion roots leading to improved plant growth and nutrient uptake. However, after maximum growth, the effects of treatment may have reduced, in line with results of Olfati et al 46 , who stated that the number of leaves per plant and other growth parameters in garlic reached their maximum values three weeks before harvesting stage and then decreased. Plants growing on soils that have received compost and/or mycorrhiza had the greatest bulb diameter compared to those of developing on soil without compost or mycorrhiza.…”
Section: Discussionsupporting
confidence: 79%